1970
DOI: 10.1103/physrevc.2.763
|View full text |Cite
|
Sign up to set email alerts
|

Neutrons Emitted in Spontaneous Fission ofCm246

Abstract: The value of v for 246Cm was found to be 3.20+ 0.22 in a BF3 proportional counter calibrated with a Cf standard.The average number of prompt neutrons v emitted per fission has been measured for the actinides in several different ways. ' ' Most measurements have been on induced fission of the isotopes U, 2 U, and Pu, which are important to reactors. Although the spontaneous fissioning of some even isotopes has been studied, and values have been obtained for isotopes through mass 254, there is little reported o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 6 publications
2
54
0
Order By: Relevance
“…As illustrated in figure 2.4b, this means that at some point in time, there is a population of small grains and large grains and the shape of the grain size distribution is not time-invariant. In literature, this growth mode is referred as abnormal grain growth and since abnormal grain growth often occurs after significant normal grain growth, it is also known as secondary grain growth [61]. There can be several reasons why in most of the cases abnormal grain growth is observed instead of normal grain growth.…”
Section: Normal and Abnormal Grain Growth In Thin Filmsmentioning
confidence: 99%
“…As illustrated in figure 2.4b, this means that at some point in time, there is a population of small grains and large grains and the shape of the grain size distribution is not time-invariant. In literature, this growth mode is referred as abnormal grain growth and since abnormal grain growth often occurs after significant normal grain growth, it is also known as secondary grain growth [61]. There can be several reasons why in most of the cases abnormal grain growth is observed instead of normal grain growth.…”
Section: Normal and Abnormal Grain Growth In Thin Filmsmentioning
confidence: 99%
“…This indicates the kinetically favored orientational stacking of ZnPc molecules in the film. The theoretical model given by Hillert [32][33][34] to describe the normal grain growth mechanism, iṡ…”
Section: Growth Mechanism Of Znpc Lb Thin Film On Annealingmentioning
confidence: 99%
“…We already reported that grain enlargement of poly-Si under the solid phase occurs upon multishot laser irradiation at low energy density. The theory of secondary grain growth by the solid phase was studied by Thompson,31) who assumed that the driving force of secondary grain growth is the energy of the grain boundary and film surface. Our proposed model also assumes the solid phase process.…”
Section: Crystallization Modelmentioning
confidence: 99%